What Role for Carboxytherapy in the Treatment of Acne Scars? - Joana Peixoto; Joana Resse Lascasas; Sofia Vedor (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Introduction: Acne is an extremely prevalent condition. The healing of active acne lesions may result in the development of scars. Atrophic scars are the main scars caused by acne and result from the degradation of collagen fibers. Carboxytherapy is a minimally invasive method that involves the application of carbon dioxide subcutaneously through small infiltrations in the skin, which improves scar tissue by increasing collagen's deposition and reorganization. The aim of this study is to review the role of carboxytherapy in the treatment of atrophic facial scars, alone or in combination with other techniques. Methods: A literature search was conducted on several databases using MeSH terms "carboxytherapy", "carbon dioxide/therapy" and "wounds" for guidelines, systematic reviews, randomized controlled trials, and observational studies, published over the last 20 years in Portuguese, English or Spanish languages. Results: A total of 129 articles were retrieved, of which four experimental studies and one case series were selected. Comparing the techniques of microneedling and carboxytherapy, both were considered non-invasive treatment modalities with equal effectiveness, tolerability and safety, resulting in similar histopathological changes. On the other hand, despite the improvement of acne scars in both treatment modalities, the results were significantly better in favor of carbon dioxide fractional laser, despite having more side effects than carboxytherapy. When these techniques are combined and carboxytherapy is used as a subcision method, there is a more marked and rapid improvement in the appearance of acne scars. Discussion: Carboxytherapy is a promising modality in the treatment of atrophic acne scars, alone or in combination with other techniques.